2011
DOI: 10.1063/1.3658861
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic anisotropy and stacking faults in Co and Co84Pt16 epitaxially grown thin films

Abstract: A combined set of experimental and theoretical diffraction studies are performed to evaluate the possible impact of stacking faults on magnetic anisotropy using epitaxially grown Co/Ru and Co 84 Pt 16 /Ru thin films on MgO(111) single crystal substrates. A 3rd nearest neighbor interaction is incorporated into Monte Carlo simulations of faulted film growth used to predict (10.L) diffraction profiles. These are compared with experimental profiles to determine stacking fault content. It is found that stacking fau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Experimental [3,7,8,28] and theoretical [29] proofs of the influence of the crystal symmetry (hcp and fcc) of Co based nanostructures on the effective anisotropy, have been widely reported for both the magnetocrystalline term and the shape one. These terms have demonstrated a big influence on the uniformity of the magnetization reversal mechanism [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental [3,7,8,28] and theoretical [29] proofs of the influence of the crystal symmetry (hcp and fcc) of Co based nanostructures on the effective anisotropy, have been widely reported for both the magnetocrystalline term and the shape one. These terms have demonstrated a big influence on the uniformity of the magnetization reversal mechanism [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Co-Pt phase alloy thin film with lower Pt content was found to be an alternative to L1 0 -FePt due to a similar K u and low ordering temperature [13][14][15][16]. From the Co-Pt binary phase diagram [17], the phase formation temperature for hexagonal-closed-packed (HCP) phase is about 300-400°C, which is lower than 500-600°C of L1 0 -FePt phase.…”
Section: Introductionmentioning
confidence: 99%
“…The layer structure of the samples was: glass/ Ni 50 Ta 50 (20 nm)/ Ni 90 W 10 (6 nm)/ Ru (20 nm)/ Magnetic layer (20 nm)/ Carbon (7 nm 10 /Ru underlayers were first deposited under argon gas pressure of 0.6 Pa at room temperature and then heated at around 700 o C to complete structural relaxation of the underlayers. The underlayers were then cooled down in the vaccum chamber and magnetic layers were deposited under argon gas pressure of 2.0 Pa at a constant heating temperature of 300 o C. The crystal diffraction structure of the magnetic layer was examined by an X-ray diffractometry (XRD) using Cu-K α radiation.…”
Section: Methodsmentioning
confidence: 99%
“…In general, to further increase K u of a CoPt alloy film, the approach of increasing spin-orbital interaction is considered effective. Many researchers reported that the enhancement of the spin-orbital interaction can be realized by the formation of a perfect hcp stacking structure (-A-B-A-B) without stacking faults (SFs) 4,[7][8][9][10][11] and the realization of a compositionally modulated atomic layer structure. 12,13 One of the methods to achieve these kinds of structures is the application of a substrate heating process during sputtering the CoPt alloy film to promote atomic migration to induce the regularity of the atomic layer sequence and site arrangement.…”
Section: Introductionmentioning
confidence: 99%